3 - State Failure, Crisis of Governance and Disengagement from the State in Africa: https://doi.org/10.4314/ad.v34i3-4.63527 - Animashaun, Mojeed Adekunle (Africa Development, 2009)
The post-colonial state in Africa has continued to dominate the public space on the continent in spite of its well advertised failings. It is widely acknowledged in the literature that the African state has utterly failed in achieving material advancement for its people, leading disenchanted and frustrated citizens to take a ‘flight’ from the state and develop parallel structures to tend to their socio-economic and cultural needs. This situation, symptomatic of a crisis of governance, provides immediate explanation for the contested character of Africa’s public sphere. This paper examines the nature of contestation in Africa’s public sphere between the two dominant actors in the sphere – the state and civil society, the ideological underpinnings of this contestation and the impact of domestic and external contexts on the contestation. The paper observes that the declining capacity of the state for social provisioning provides the context for citizens’ withdrawal from the public space occupied by the state. The paper argues that disengagement from the state, apart from not serving the interest of both the state and civil society, has serious implications for governing Africa’s public sphere.